Structural Studies on the Smallest Unit of Nanocarbons, C2: DFT and ab initio Calculations - KASSAEE, M.Z.; GHAVAMI, M.; VESSALLY, E.; CHEHMEHKANI, A. (Asian Journal of Chemistry, 2010)
The total energies and the energy differences of 3 states (singlet, triplet and quintet) of C2 with 19 methods have been calculated. The energy results of triplet and quintet are more or less compatible between old and advanced methods. Surprisingly, the results of energies of singlet and triplet states are contradicted between old and advanced methods. Anyway, the singlet state of C2 is more stable than triplet state with the advanced methods. The bond hybridization of 3 states is calculated by CBSQ/ 6-311++G** level of theory.